Indicator for Analysis of Tolerance of Unabi Trees to Soil-Climatic Conditions - Sokhib Yakshibekovich Islamov; Dilnoza Raimovna Raimova (Web of Journals Publishing, 2023)
The article deals with the analysis indicators of the tolerance of unabi trees to soil and climate conditions.
Keywords: Unabi daraxti, tuproq-iqlim, sharoit, bardoshlik, tahlil, ko’rsatkich.